PREDATORY PRICING PROMO OJEK ONLINE DALAM PRESEPEKTIF HUKUM PESAING USAHA - B.A.P, R.Bima Avriliano Dody; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
In today's modern era, many people in general use and take advantage of the sophistication of communication technology, especially in the field of business economics, one of which is online motorcycle taxi transportation. online motorcycle taxis are gojek, gojek has many promos that are applied such as discounted prices, promo vouchers, and many more. and in this case predatory pricing contradicts Article 20 of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The formulation of the problem in this research are: 1.) What are the legal consequences (predatory pricing) that arise from the perspective of business competition law? , 2.) Are the promos of online motorcycle taxi applicators not in conflict with the concept of predatory pricing in business law competition?. The conclusions obtained are, firstly, the Gojek promo contradicts the concept of predatory pricing in business competition, because it must be distinguished between promotional activities in business activities and the concept of price fixing which is prohibited in business competition law. is a program of a special offer company in the short term to determine the promotion of related consumers in order to make a faster purchasing decision. Sales promotion is a supporting activity of advertising. After and get information from a product, consumers will be more interested and interested in the decision after getting a special offer to see what is offered from the product or service